United States policy towards the International Criminal Court. Selected legal issues - Kupis, Paweł Aleksander (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
This article analyzes the United States policy towards the International Criminal Court while focusing on the selected legal issues. The author starts with an introduction to the history of international criminal prosecutions, in particular — the creation of the International Criminal Court. It discusses alleged inconsistencies of the Rome Statute with international law, legal effects of the US signature of the Statute, as well as domestic and international actions of the US regarding protection of its citizens and regulating the cooperation with the ICC. In conclusion the author argues that it is unlikely that the US will rectify the Rome Statute.
Keywords: Stany Zjednoczone Ameryki Północnej; międzynarodowe prawo karne; Międzynarodowy Trybunał Karny; globalna sprawiedliwość